2014
DOI: 10.1186/preaccept-1989848861132152
|View full text |Cite
|
Sign up to set email alerts
|

Aging exacerbates damage and delays repair of alveolar epithelia following influenza viral pneumonia

Abstract: Background: Influenza virus infection causes significantly higher levels of morbidity and mortality in the elderly. Studies have shown that impaired immunity in the elderly contributes to the increased susceptibility to influenza virus infection, however, how aging affects the lung tissue damage and repair has not been completely elucidated. Methods: Aged (16-18 months old) and young (2-3 months old) mice were infected with influenza virus intratracheally. Body weight and mortality were monitored. Different da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…As a result, loss of tissue integrity allows the lungs to be more susceptible to secondary bacterial infections. This is also shown in a mouse model where the aged mouse exhibits exacerbated damage of lung tissues and alveolar epithelia following influenza virus and pneumonia infection (Yin et al, 2014;Liew et al, 2014).…”
Section: Complications Of Secondary Bacterial Infections In the Elderlymentioning
confidence: 92%
“…As a result, loss of tissue integrity allows the lungs to be more susceptible to secondary bacterial infections. This is also shown in a mouse model where the aged mouse exhibits exacerbated damage of lung tissues and alveolar epithelia following influenza virus and pneumonia infection (Yin et al, 2014;Liew et al, 2014).…”
Section: Complications Of Secondary Bacterial Infections In the Elderlymentioning
confidence: 92%
“…COPD is a disease that accelerates aging of the lungs and is closely associated with other aging effects [76]. Aging leads to a decrease in the number and activity of stem cells in the trachea tissue and a consequence is a significant decrease in the ability to repair tissue [77]. Elderly patients with COPD have significantly reduced stem cell numbers and activity.…”
Section: Application Of Msc Therapy For Copdmentioning
confidence: 99%
“…Few studies have looked into the effect of ageing on lung stem cells. Yin et al () showed that influenza viral infections cause a more extensive loss of alveolar type 1 (AT1) and type 2 (AT2; stem) cells and delayed recovery of AT2 cells in aged mice. Furthermore, Wansleeben, Bowie, Hotten, Yu, and Hogan () showed that ageing results in fewer tracheal basal stem cells, although it did not result in their functional impairment when examined in an in vitro assay and with an in vivo injury model.…”
Section: Introductionmentioning
confidence: 99%